(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The insurance companies are one of the organizations that rely mainly on human capital to underwriting to insurable risks because most of risks have many variables, so the aim of the research is to show the level of interest of the researched company in human capital, the reality of the underwriting policy in it, and the relationships of correlation and effect between them, and the approach has been used Analytical descriptive, as books, research and other related sources were used for the purpose of completing the theoretical side, on the practical side, a questionnaire was prepared, which represents the main tool for collecting data and distributed to a random sample of 64 people from underwriting managers and employees in specialized insurance branches as well as The technical department at the National Insurance Company, and in order to analyze the data and obtain the results, a number of statistical methods were used in proportion to the nature of the collected data, by means of the (SPSS) program to calculate the statistical indicators, and one of the most prominent results reached by the research is the presence of significant correlation and effect between The two variables, The research also presented a set of recommendations to the company on both human capital and achieving the underwriting policy.